The developmental transition of ovine adipose tissue through early life. (28th January 2013) - Pope, M.; Budge, H.; Symonds, M. E.
Abstract Aim Hypothermia induced by cold exposure at birth is prevented in sheep by the rapid onset of non‐shivering thermogenesis in brown adipose tissue (BAT). Changes in adipose tissue composition in early life are therefore essential for survival but also influence adiposity in later life and were thus examined in detail during early development. Methods Changes in adipose composition were investigated by immunohistochemistry and qRT‐PCR between the period from the first appearance of adipose in the mid gestation foetus, through birth and up to 1 month of age. Results We identified four distinct phases of development, each associated with pronounced changes in tissue histology and in distribution of the BAT specific uncoupling protein (UCP)1. At mid gestation, perirenal adipose tissue exhibited a dense proliferative, structure marked by high expression of KI‐67 but with no UCP1 or visible lipid droplets. By late gestation large quantities of UCP1 were present, lipid storage was evident and expression of BAT‐related genes were abundant (e.g. prolactin and β3 receptors). Subsequently, within 12 h of birth, the depot was largely depleted of lipid and expression of genes such as UCP1, PGC1α, CIDEA peaked. By 30 days UCP1 was undetectable and the depot contained large lipid droplets; however, genes characteristic of BAT (e.g. PRDM16 and BMP7) and most characteristic of white adipose tissue (e.g. leptin and RIP140) were still abundant. Conclusion Adipose tissue undergoes profound compositional changes in early life, of which an increased understanding could offer potential interventions to retain BAT in later life.